Nano‐Octahedron Cobalt Oxide Decorated Graphene Nanocomposites for the Selective/Simultaneous Detection of Dopamine - Swathi Tharani Dharmalingam; Mushtaq Ahmad Dar; Rukhsana Gul; Manickam Minakshi Sundaram; Ibrahim Abdullah Alnaser; R. Sivasubramanian (Advanced Materials Interfaces)
Abstract Nano‐octahedron cobalt oxide decorated graphene nanocomposite is reported in this work for selective and simultaneous determination of dopamine (DA) and uric acid (UA). The composite is synthesized using a hydrothermal method and characterized to identify the crystal structure and its shapes. The Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) images indicate the silhouette image of the nanocube decorated over graphene oxide. The Gr‐Co₃O₄/glassy carbon electrode (GCE) is utilized for the electrochemical detection of dopamine (DA). Cyclic voltammetry (CV) studies revealed a significant breakthrough such as Gr‐Co₃O₄/GCE exhibited higher electrocatalytic activity for DA oxidation than the bare GCE. Differential pulse voltammetry (DPV) measurements demonstrated a detection limit of 0.09 µM for DA, with a linear response range from 1 to 500 µM. For uric acid (UA), the detection limit and linear range are estimated as 0.2 and 100 to 8000 µM, respectively. The sensor selectively detects DA in the presence of UA is confirmed, with a peak separation of 250 mV between DA and UA. The reliability of the sensor is validated through using human serum specimens, paving the way for exciting potential applications in biomedical research and clinical diagnostics.